The Rise Of Robo-Advisors: Ai-Powered Investment Management For Everyone (Journal of Namibian Studies : History Politics Culture, 2022)
An understanding of this research is crucial for several factors. First, it offers a great brief to recent advancements in investment management due to the incorporation of technological innovation such as artificial intelligence (AI) and algorithm trading. Second, it involves a comprehensive comparative assessment of robot-advisors and conventional financial consultants, which may help potential buyers understand and compare two promising services. This comparison shows efficiency, price-level, and availability in robot-advisors as those may serve more users with low initial capital, including youths. Further, the analysis is expanded to further discuss the implications of fintech, with a focus on the potential of artificial intelligence for changing investor behaviour and regulatory environment as well as for redesigning the financial advisory services. In this respect, the research fills the gap by examining the abovementioned aspects to reveal the characteristics of robot-advisors and their potential for revolutionizing the field of investment management. By doing so, this research expected to be valuable to investors, financial advisors and policymakers in order to understand the opportunities and risks that can arise from the use of AI in the financial service industry.